Garlic against Heart-related Ailments: Chemistry, Pharmacology, and Future Perspective - Chaurasia, Pankaj K.; Bharati, Shashi Lata; Singh, Sunita (Mini Reviews in Medicinal Chemistry, 2024)
Background: Allium sativum L. (Garlic) is a well-recognized plant of great nutraceutical value with pharmacological evidences. It is full of dietary as well as pharmaceutical properties and has been used in traditional medications for a long time. It is known for good antioxidant, antifungal, antibacterial, anti-diabetic, anti-inflammatory, anticancer, and antiviral effects, along with other therapeutic roles in cardiovascular diseases, anti-atherosclerotic, antihypertensive, anti-thrombotic, blood pressure, bone and skin related problems etc. Objective: Considering the potential of garlic in the treatment of cardiovascular/heart-related diseases, the main objective of this study was to prepare a subject-centric mini-review focusing on its chemistry and pharmacology in heart-related issues. Methods: In order to prepare this mini-review article, an extensive online literature search was performed to find out the most recent studies related to this topic. These studies were briefly reviewed, assessed, and discussed to explore the possible capability of garlic for the cure of cardiovascular problems. Result: Several experiments on mice models, rat models as well as on humans show the effective role of various forms of garlic in cardiovascular or heart-related ailments. After reviewing the available publications on garlic in heart-related issues, authors found that garlic and its sulfur (S)-based organic constituents may have advantageous applications in the treatment of cardiovascular diseases.
Keywords: cardiovascular disease